Department of Dynamic Systems of Saratov State University on the basis of the SB IRE RAS — 25 years - Kuznetsov, Aleksandr Petrovich; Ryskin, Nikita Mikhailovich (Известия высших учебных заведений: Прикладная нелинейная динамика, 2024)
In 2023, the Department of Dynamic Systems of Saratov State University on the basis of the Saratov branch of the Institute of Radio Engineering and Electronics of the Russian Academy of Sciences turned 25 years old. During this time, the department prepared training courses "Nonlinear oscillations," "Theory of catastrophes," "Dynamic systems and bifurcations," "Dynamic chaos," "Mathematical methods of nonlinear physics" and others. A series of textbooks and taskbooks in the relevant areas has been released.